A Revised Bloom’s Taxonomy Based Analysis of Elementary School English Teaching Curriculum - Kuloğlu, Ayşenur; Tutus, Fatma (My University, 2024)
This study evaluates the learning outcomes in secondary education English Curriculums regarding knowledge and cognitive process in Revised Bloom Taxonomy. Document analysis was adopted as a qualitative research method in data analysis. A total of 245 learning outcomes was studied, 52 of which were in grade 5, 60 in grade 6, 63 in grade 7 and 70 in Grade 8. As a result of research it was seen that most of the outcomes, belonging to 5, 6, 7, and 8th grade English teaching curriculum, were at the dimension of “conceptual knowledge” of Revised Bloom Taxonomy’s knowledge dimension. According to the conceptual knowledge dimension, the most outcomes were seen at the “applying”. An analysis of the results suggested that knowledge and cognitive process were not evenly distributed in English courses. The results pointed out that most of the learning outcomes accounted for “conceptual knowledge” in grade 5, 6, 7 and 8 level English courses. In terms of the “cognitive process”, the most frequent one is was the “applying” section. Applying increased as a learning outcome in grade 5, 6 and 7, whereas analysis and creation are were included in learning outcomes for grade 8 and advanced thinking. However, the cognitive process failed to increase in the learning outcomes from grade 5 to 7. Hence, it is possible to suggest that the distribution of learning outcomes be planned carefully based on the students’ levels
Keywords: Document analysis; Revised Bloom’s Taxonomy; Lower secondary education English teaching curriculum